Adherence to prophylaxis in adolescents and young adults with severe haemophilia A, a qualitative study with patients. Issue 1 (1st January 2018) - van Os, S.; Troop, N.; Ryder, N.; Hart, D. P.
ABSTRACT: Introduction: Reported levels of adherence to prophylaxis among young people with haemophilia (YPH) vary widely and are predominately based on estimations made by healthcare professionals and parents. Reasons for (non)adherence among YPH in particular have not been evidenced. Aim: to examine experiences in relation to prophylaxis with YPH themselves, and barriers and facilitators to their adherence. Methods: 11 Participants were recruited in five haemophilia centres across England and Wales. All patients who met the inclusion criteria (aged 12-25, diagnosed with haemophilia, on prophylaxis) were approached during a routine check-up appointment, and all participants who agreed to take part were interviewed. Interviews were audio recorded, transcribed and analysed using Interpretative Phenomenological Analysis. Results: Self-reported adherence to prophylaxis was good. Few participants admitted to intentionally skipping injections although they reported sometimes forgetting. However, due to the increasingly personalised and flexible approach to prophylaxis, adherence is not straightforward to define. Barriers to adherence included a busy lifestyle, dislike of the intravenous injection, venous access issues, anxiety or stress and being out of one's normal routine. Support was an important facilitator to adherence, including support from health professionals at the haemophilia centre as well as friends. Parents appear to be very involved with their child's haemophilia management, even after they leave home. Conclusion: What this study adds is that the increasingly flexible and personalised approach to managing prophylaxis in haemophilia may sometimes lead to confusion around treatment frequency and dosing. This may lead to accidental non-adherence, which is distinct from both skipping and forgetting. Advice from haemophilia teams may not always be consistent and is likely to be interpreted differently by different individuals. Some additional training and education of patients and their families to increase their knowledge and skills around prophylaxis may reduce this confusion and therefore is likely to improve adherence further.